A companion to Thomas Jefferson - Cogliano, Francis D. (Blackwell companions to American history., 2012)
"A Companion to Thomas Jefferson presents a comprehensive assessment and overview of the life and legacy of Thomas Jefferson through a collection of essays grounded in the latest scholarship. Works from more than thirty leading scholars explore specific themes concerning the extraordinary life and times of the influential Founding Father and third U.S. President. Jefferson's wide range of interests and expertise, are explored, along with his lengthy and multifaceted public career. Other essays delve into elements of Jefferson's private life, including his controversial relationship with Sally Hemings. The essays also consider Jefferson and American democracy, slavery, Native Americans, and his writings such as the Summary View of the Rights of British America, The Declaration of Independence, and Notes on the State of Virginia. A Companion to Thomas Jefferson represents a comprehensive portrait of the elusive and contradictory figure who continues to hold sway in the public imagination and occupies a central place in American history"--